Longitudinal study of health, disease and access to care in rural Victoria: the Crossroads-II study: methods - Kristen M. Glenister; Lisa Bourke; Leslie Bolitho; Sian Wright; Stuart Roberts; William Kemp; Leigh Rhode; Ravi Bhat; Sönke Tremper; Dianna J. Magliano; Mike Morgan; Rodrigo Mariño; et al. (BMC, 2018)
Abstract Background High quality, contemporary data regarding patterns of chronic disease is essential for planning by health services, policy makers and local governments, but surprisingly scarce, including in rural Australia. This dearth of data occurs despite the recognition that rural Australians live with high rates of ill health, poor health behaviours and restricted access to health services. Crossroads-II is set in the Goulburn Valley, a rural region of Victoria, Australia 100-300 km north of metropolitan Melbourne. It is primarily an irrigated agricultural area. The aim of the study is to identify changes in the prevalence of key chronic health conditions including the extent of undiagnosed and undermanaged disease, and association with access to care, over a 15 year period. Methods/design This study is a 15 year follow up from the 2000-2003 Crossroads-I study (2376 households participated). Crossroads-II includes a similar face to face household survey of 3600 randomly selected households across four towns of sizes 6300 to 49,800 (50% sampled in the larger town with the remainder sampled equally from the three smaller towns). Self-reported health, health behaviour and health service usage information is verified and supplemented in a nested sub-study of 900 randomly selected adult participants in 'clinics' involving a range of additional questionnaires and biophysical measurements. The study is expected to run from October 2016 to December 2018. Discussion Besides providing epidemiological and health service utilisation information relating to different diseases and their risk factors in towns of different sizes, the results will be used to develop a composite measure of health service access. The importance of access to health services will be investigated by assessing the correlation of this measure with rates of undiagnosed and undermanaged disease at the mesh block level. Results will be shared with partner organisations to inform service planning and interventions to improve health outcomes for local people.